2018
DOI: 10.3389/fgene.2018.00040
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameter Estimates for Metabolizing Two Common Pharmaceuticals in Swine

Abstract: In livestock, the regulation of drugs used to treat livestock has received increased attention and it is currently unknown how much of the phenotypic variation in drug metabolism is due to the genetics of an animal. Therefore, the objective of the study was to determine the amount of phenotypic variation in fenbendazole and flunixin meglumine drug metabolism due to genetics. The population consisted of crossbred female and castrated male nursery pigs (n = 198) that were sired by boars represented by four breed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Additionally, our estimated V ss is consistent with previously reported values in swine ( 23 ). The heritability of the pigs was not within the scope of this project, however, a previous study has shown that heritability can have an effect on FM PK parameters, which may explain the two drug metabolism groups ( 30 ). Additionally, the stress that can be induced by repeated blood collections, individual housing, and early weaning could contribute to differences in drug metabolism ( 31 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, our estimated V ss is consistent with previously reported values in swine ( 23 ). The heritability of the pigs was not within the scope of this project, however, a previous study has shown that heritability can have an effect on FM PK parameters, which may explain the two drug metabolism groups ( 30 ). Additionally, the stress that can be induced by repeated blood collections, individual housing, and early weaning could contribute to differences in drug metabolism ( 31 ).…”
Section: Discussionmentioning
confidence: 98%
“…Plasma concentration axes were scaled by ln ("plasma concentration" + 1) to improve resolution of plasma concentrations close to zero, as previously described (19). study has shown that heritability can have an effect on FM PK parameters, which may explain the two drug metabolism groups (30). Additionally, the stress that can be induced by repeated blood collections, individual housing, and early weaning could contribute to differences in drug metabolism (31).…”
Section: Discussionmentioning
confidence: 99%
“…Pigs also exhibit many human-relevant behaviors, such as social structure, enabling the investigation of complex cognitive functions that are often impaired in human neurological disorders such as learning, memory, and social behavior [ 32 , 33 , 34 ]. Moreover, the pig’s physiology and metabolism are closer to humans compared to smaller animal models, enabling a more accurate evaluation of pharmacokinetics and treatment responses [ 35 , 36 ]. Collectively, these factors make the pig a valuable model for studying human neurological conditions and injury, facilitating the translation of preclinical findings to clinical applications, and enhancing our understanding of these complex disorders.…”
Section: Reviewmentioning
confidence: 99%